Byproducts of the nut and peanut agro-industry as sources of phytochemicals suitable for the nutraceutical and food industries - Vázquez-Flores, Alma A. (Apple Academic Press / CRC Press, 2018)
Nut by-products are the materials discarded from the peeling process of edible peanuts and tree nuts such as almonds, pistachio, pecans, and hazelnuts. These by-products constitute more than 50% of the total weight generated by the nut industry and represent a large amount of solid waste to handle by the producers. Currently, few useful strategies, with low or nule-added value, exist for disposal of these by-products. Some authors point out that there are more ambitious applications for their uses. They are an excellent source of phenolic compounds and dietary fiber with potential applications, not only as nutraceuticals or functional food ingredients to protect human health but also to enhance shelf life or quality of several foodstuffs when used as natural additives. The aim of this chapter is to review the nutraceutical potential of phytochemicals from nut by-products, their physiological effects in human health, and their use in the food industry